KADAR KALSIUM DAN SIFAT ORGANOLEPTIK TAHU SUSU DENGAN VARIASI JENIS BAHAN PENGGUMPAL - Nurhidajah -; Agus Suyanto (Universitas Muhammadiyah Semarang, 2012)
Curd is one of the dairy products into a product out using a coagulant, the curd is one source of calcium. The type of coagulant is one important factor in making the curd. This study aims to determine the level of calcium and the organoleptic properties of the curd with variations in the type coagulanttreatment. This study uses a completely randomized design (CRD) with 4 treatment monofaktor the type of coagulant pineapple juice, vinegar, citric acid, gypsum. Each experiment carried repeat 5 times. Making curd with variations in the type of coagulant pineapple juice 5%, 5% acetic acid, 5% citric acid, gypsum 2% per 1 liter of milk, having obtained a blob out, filtering and pengeperesan to form the curd. Making curd with the type of coagulant gypsum give optimum results based on the levels of calcium and the yield, will be used for organoleptic test. This test is performed on flavor, texture, color, flavor with hedonic methods. ANOVA statistical test research results showed levels of calcium, yieldand resilience significantly affect the curd from a wide variety of coagulant. Suppleness curd most preferred are of the type of coagulant vinegar. Results of statistical test to organoleptic properties is obtained; coagulant material variation does not affect the aroma and taste, but the effect on the textureand color. Keywords: curd, calcium, organoleptic properties, coagulant